Dramatic thermostabilization of yeast iso-1-cytochrome c by an asparagine----isoleucine replacement at position 57. - Das, G (1989)
Two Saccharomyces cerevisiae yeast mutants, cyc1-73 and cyc1-190, contain nonfunctional and presumably unstable forms of iso-1-cytochrome c due to Gly-34----Ser and His-38----Pro replacements, respectively. Second-site reversions that produced Asn-57----Ile replacements at least partially restored function, presumably by alleviating the instability of these two altered iso-1-cytochromes c. Introduction of the Ile-57 replacement by site-directed mutagenesis in an otherwise normal protein resulted in a 17 degrees C increase in the transition temperature (Tm), corresponding to over a 2-fold increase in the free energy change (delta G degrees) for thermal unfolding.